2023
DOI: 10.3390/antibiotics12020332
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Helicobacter pylori Resistance to Antibiotics: A Topic of Increasing Concern

Abstract: Antibiotic resistance among Helicobacter pylori strains is the major cause of eradication failure. Resistance prevalence is dynamic and can greatly vary among countries over the years. We revealed H. pylori resistance trends for five antibiotics in 14 countries through articles predominantly published in 2018–2022, since the latest data can best show the most recent trends in resistance evolution. Amoxicillin resistance generally exhibited no evolution, yet it increased in Bulgaria, Iran, China, and Vietnam. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 64 publications
1
55
0
1
Order By: Relevance
“…Antibiotics used in first-line PPI-TT are clarithromycin, amoxicillin and metronidazole or, more restrictive, levofloxacin and, in selected cases, furazolidone. Treatment failures with PPI-TT occur with increasing frequency and are primarily related to antibiotic resistance, insufficient acid suppression and inadequate adherence to medications 10,[251][252][253] . Acid suppression with PPI (omeprazole, esomeprazole, lansoprazole, pantoprazole or rabeprazole in double standard dose) is essential and aims to raise intragastric pH to 6 or higher, which optimizes the stability, bioavailability and efficacy of antibiotics 254,255 .…”
Section: Ppi Triple Therapymentioning
confidence: 99%
“…Antibiotics used in first-line PPI-TT are clarithromycin, amoxicillin and metronidazole or, more restrictive, levofloxacin and, in selected cases, furazolidone. Treatment failures with PPI-TT occur with increasing frequency and are primarily related to antibiotic resistance, insufficient acid suppression and inadequate adherence to medications 10,[251][252][253] . Acid suppression with PPI (omeprazole, esomeprazole, lansoprazole, pantoprazole or rabeprazole in double standard dose) is essential and aims to raise intragastric pH to 6 or higher, which optimizes the stability, bioavailability and efficacy of antibiotics 254,255 .…”
Section: Ppi Triple Therapymentioning
confidence: 99%
“…The latest systematic review and meta-analysis in 2018 reported that the primary amoxicillin resistance in H. pylori has a generally low prevalence (≤10 %) in all World Health Organisation regions, except in the Eastern Mediterranean region (14 %) [7]. However, according to the latest review by Boyanova et al [8], a trend of rising amoxicillin resistance was detected in various countries including China (from 4.3 % in 1998-1999 to 25.9 % in 2016-2017) [9], Iran (from 9.0 % in 1999-2000 to 36.0 % in 2017-2019) [10], Vietnam (from ≤1.1 % in 2013-2015 to 25.7 % in 2020) [11] and Bulgaria (from 4.2 % in 2007-2014 to 8.9 % in 2015-2021) [12]. In Malaysia, consistent reports published between 2011 to 2019 showed a 0 % rate for both primary and secondary amoxicillin resistance [13][14][15][16][17] until a recent study reported a 3.9 % (2/51) secondary resistance rate in 2022 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the resistance is still rather low, 13 a significant increase in overall amoxicillin resistance was detected in patients form Bulgaria, China, Vietnam, and Iran. 14 Therefore, using amoxicillin in combination is highly recommended to enhance its eradication efficacy against H. pylori than in single agent use. 15 Therefore, we manage to modify the parent amoxicillin drug to a new compound conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori is associated with mucosa‐associated lymphoid tissue (MALT) lymphoma as well. Although the resistance is still rather low, 13 a significant increase in overall amoxicillin resistance was detected in patients form Bulgaria, China, Vietnam, and Iran 14 . Therefore, using amoxicillin in combination is highly recommended to enhance its eradication efficacy against H. pylori than in single agent use 15 .…”
Section: Introductionmentioning
confidence: 99%